An efficient approach for improving granular cold water soluble starch properties using energetic neutral atoms treatment and NaOH/urea solution. (August 2023) - Sudheesh, Cherakkathodi; Sunooj, Kappat Valiyapeediyekkal; Navaf, Muhammed; Akhila, Plachikkattu Parambil; Aaliya, Basheer; Mounir, Sabah; Sinha, Suraj Kumar; Kumar, Sunny; Sajeevkumar, Vallayil Appukuttan; George, Johnsy
Abstract: The granular cold water soluble starch (GCWSS) was prepared from energetic neutral (EN) atoms treated kithul starch using the alkali/urea aqueous solution, and their properties were analysed. During preparation, significant morphological changes in the starch granules by cold plasma treatment facilitated the diffusion of alkali/urea solution. The plasma treatment induced a change from the A-type allomorph to a more amorphous structure, and the structural changes of GCWSS from cold plasma-treated starch improved their cold water solubility. The GCWSS from the kithul starch sample treated at 20W (EN-20W) exhibited the lowest amylose content, and their oil absorption capacity, moisture absorption and enzymolysis were considerably improved. The effect of alkali/urea solution on the plasma-treated starch decreased the storage modulus (G′), loss modulus (G″) and complex viscosity (Ƞ*) of GCWSS, representing their poor gelation due to lower retrogradation. The decrease in hardness and higher freeze-thaw stability and paste clarity also indicated their inferior ageing property. Therefore, this research provides an understanding of the use of EN atom treatment prior to the GCWSS preparation using the alkali/urea system. Graphical abstract: Image 1 Highlights: Kithul starch exhibited severe morphological changes after cold plasma treatment. Cold water solubility significantly (p ≤ 0.05) increased with cold plasma power. Amylose content was markedly reduced in GCWSS (granular cold water soluble starch). GCWSS prepared from plasma treated starch showed improved enzymolysis. Retrogradation property was highly reduced in GCWSS prepared from treated starch.